Scaling up polychaete contributions to estuarine ecosystem functions - Amanda Martins; Marcos Krull; Francisco Barros (Discover Ecology, 2026)
Ecosystem-level estimates of estuarine macrobenthos functions are scarce in the literature, with most estimates conducted at small spatial scales. This study estimates two important functions (organic matter decomposition and bioturbation) performed by polychaetes across a tropical estuarine system. Bayesian generalized linear mixed models were used to estimate polychaete abundance throughout the system, combined with species-specific measurements of organic matter decomposition and bioturbation. A long monitoring dataset was used to build the abundance models, which were integrated with data resulting from bioturbation and organic matter laboratory experiments, involving seven different polychaete families. We estimated that polychaetes consume, on average, 232.6 tons of organic material and bioturbate 6,098.3 m 3 of sediment over 96 h across a 23.7 km² area, representing the contribution of approximately two billion individuals. The higher estimates of functions were found in regions with elevated salinity, with one family (Orbiniidae) being responsible for most of the functions delivered in the system. Additionally, we observed correlations between most of the polychaetes in functional contributions throughout the system. Functional redundancy was higher in marine zones (euhaline) than in upstream (oligohaline), with fewer polychaetes contributing to these functions. We demonstrate how laboratory experiments can be combined with monitoring data sets to estimate ecosystem-level functioning.